1978
DOI: 10.1136/jnnp.41.12.1092
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological aspects of sensory conduction velocity in healthy adults. 1. Conduction velocity from digit to palm, from palm to wrist, and across the elbow, as a function of age.

Abstract: SUMMARYThe sensory conduction velocity from digit to palm and from palm to wrist was determined in median (digit 3) and ulnar (digit 5) nerves in 47 healthy subjects with age range from 21 to 77 years. The decrement of the sensory conduction as a function of age was more marked in the palm to wrist than in the digit to palm segment. Sensory conduction velocity of the ulnar nerve across the elbow was also studied. Irregularities in the shape of the sensory evoked potential recorded above the cubital sulcus were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

1978
1978
2002
2002

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(9 citation statements)
references
References 9 publications
(16 reference statements)
1
8
0
Order By: Relevance
“…These results agree with those of Dreschler (1975), and the preferential involvement of the median nerve in the elderly could be explained by a chronic compression in the carpal tunnel, and by a higher sensitivity to anoxia of the median nerve of the limbs of older people (Dreschler, 1975). These results also agree with the conclusions of Cruz Martinez et al (1978b), and suggest that age causes changes particularly in the points where the nerves are more frequently compressed.…”
Section: Discetssioinsupporting
confidence: 89%
See 2 more Smart Citations
“…These results agree with those of Dreschler (1975), and the preferential involvement of the median nerve in the elderly could be explained by a chronic compression in the carpal tunnel, and by a higher sensitivity to anoxia of the median nerve of the limbs of older people (Dreschler, 1975). These results also agree with the conclusions of Cruz Martinez et al (1978b), and suggest that age causes changes particularly in the points where the nerves are more frequently compressed.…”
Section: Discetssioinsupporting
confidence: 89%
“…The series explored is the same as that in Cruz Martinez et al (1978b)347 healthy subjects aged from 21 to 77 years.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various physical functions are changed in aging. For example, autonomic nervous function declines (Pfeifer et al ., 1983), decrement of sensory conduction and changes in the shape of the evoked potentials to stimulation of the ulnar or median nerve (Cruz‐Martinez.A. et al ., 1978), and changes in tactile (Thornbury & Mistretta, 1981) and somesthetic sensitivity including thermal sensation (Kenshalo, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…28 It has been suggested that subclinical en-trapments are the cause of this age-related decline in NCV. 12,20 Clearly, this is not the only explanation for the reduction in NCV seen with increasing age.…”
mentioning
confidence: 94%